Given equation is 6(7b - 4) = 60 Step by Step explanation
7b - 4 = 6
7b - 4 = 10
7b = 10 + 4
7b = 14
b = 7 = 2 Answer
-Answered by ATP Admin On 09 July 2019:11:53:03 PM
You can see here all the solutions of this question by various user for NCERT Solutions. We hope this try will help you in your study and performance.
This Solution may be usefull for your practice and CBSE Exams or All label exams of secondory examination. These solutions or answers are user based solution which may be or not may be by expert but you have to use this at your own understanding of your syllabus.
Our Expert Team reply with answer soon.
Ask Your Question
* Now You can earn points on every asked question and Answer by you. This points make you a valuable user on this forum. This facility is only available for registered user and educators.
Next moment you answer is ready .... go ahead ...